PERDAGANGAN BERJANGKA KOMODITI: ASPEK FIQH DAN EKONOMI - AM Hafidz MS (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2009)
Commodity Futures Trading (CFT) essentially has hedging as a main purposes. But for some 'black investors', CFT has been used to make blind speculation that divert and distort the existence of CFT. In the Islamic economics perspective, CFT also remains a problem deals with the legal basis that can be used to justify the implementation of CFT in contemporary economy. So, this article will discuss; the nature and types of CFT; importance of CFT in modern economy; and CFT in the perspective of Islamic Economics.